A new bibenzyl and a new methylflavan from the tubers of Bletilla striata. (August 2021) - Lee, Jin Woo; Kim, Jun Gu; Lee, Dongho; Lee, Mi Kyeong; Hwang, Bang Yeon
Graphical abstract: Highlights: A new bibenzyl (1 ) and a new methylflavan (2 ) were isolated from Bletilla striata . The absolute configuration of 1 and 2 were confirmed by ECD data. Phenanthrenes 4 - 6 exhibited inhibitory effects on LPS-induced NO production. Abstract: A new bibenzyl, (+)-(1 S )-4ʹ, 5ʺ-dihydroxy-1, 3ʹ, 5ʹ, 3ʺ-tetramethoxybibenzyl (1 ), and a new methylflavan, (2 S )-7, 4′-dihydroxy-5-methoxy-8-methylflavan (2 ), together with 10 known compounds were isolated from the methanolic extract of the tubers of Bletilla striata . Their chemical structures were elucidated based on spectrometric data interpretation, especially 1D and 2D NMR, HRESIMS, and electronic circular dichroism (ECD) data. All isolates (1 - 12 ) were evaluated for their inhibitory properties on nitric oxide production induced in RAW 264.7 cells, and dihydrophenantrenes 4 and 6 exhibited the best inhibitory effects with IC50 values of 29.5, and 6.5 μM, respectively. Additionally, significant activity possessed phenantrene 5 and methylflavane 2 with IC50 values of 38.9, and 44.9 μM, respectively.